A family of reconfigurable deployable polyhedral mechanisms based on semiregular and Johnson polyhedra. (August 2018) - Li, Ruiming; Yao, Yan-an; Ding, Xilun
Highlights: Reconfigurable double angulated elements with six half-platforms are designed. The constraints, parameters and kinematics of RDAE are identified and analyzed. Based on RDAE, reconfigurable multiple angulated elements is designed. A family of RDPMs based on semiregular and Johnson polyhedra are constructed. Abstract: This paper proposes and designs reconfigurable double angulated element (RDAE) and reconfigurable multiple angulated element (RMAE). A family of reconfigurable deployable polyhedral mechanisms (RDPM) based on semiregular and Johnson polyhedra are synthesized by using RDAE and RMAE. The obtained RDPMs can deploy in Hoberman sphere motion (HSM) and Radially Reciprocating Motion (RRM). The constraint conditions and geometric parameters (angles and link lengths) of RDAE are identified by considering the constraints of two pairs of angulated elements and three intersected axes. The kinematics of RDAE in HSM mode and RRM mode are also analyzed. RMAE is further investigated with its constraints and parameters identified. The construction steps of RDPMs based on semiregular and Johnson polyhedra are introduced separately, and reconfigurable deployable triangular prismatic mechanism and reconfigurable deployable triangular cupola mechanism as two examples are constructed in computer as well as in reality to verify the feasibility of RDAE, RMAE and the proposed construction method. Graphical abstract: